Analysis of Learning Independence of Children with Special Needs - Yusi Adetia Putri; Budi Susetyo; Iding Tarsidi (Universitas Pendidikan Indonesia (UPI), 2021)
Learning independence is an important value that every student must have. Students in SLB B Budi Nurani, Sukabumi City need to be independent in the learning process, because in fact all students are not yet independent, in other words there are still students who need help from others in learning. The purpose of this study was to determine how the independent learning of children with hearing impairment in SMPLB SLB B Budi Nurani, Sukabumi City. The research method used in this research is descriptive quantitative. The independence analysis in this study was conducted on five students. In conducting this study of independent learning, researchers measured learning independence using an instrument in the form of an observation sheet. Data collection is done by means of observation, then the data obtained is then analyzed descriptively quantitatively. The conclusion of this research is that the class VIII hearing impairment child of SMPLB B Budi Nurani Sukabumi City is independent in learning. This is based on the results of research data processing which shows the percentage per indicator achieved by deaf grade VIII children is in the independent and very independent category.